“Sandwich Therapy”—Immunotherapy Plus Concurrent Chemoradiotherapy for Advanced Esophagogastric Junction Carcinoma: Report of Two Cases and Literature Review - Wu, Lei; Liu, Juan; Liang, Long; Mao, Mian; Li, Xiangpan; Li, Tao; Lang, Jinyi; Wang, Qifeng (Frontiers in Oncology, 2022)
Introduction Esophagogastric junction (EGJ) carcinomas develop in the transition zone between the esophagus and stomach. The incidence of EGJ carcinoma has steadily increased over the past few decades. Most patients are first diagnosed at an advanced stage, which renders them ineligible for surgery. Current methods for the treatment of advanced EGJ carcinoma include surgery, chemotherapy, local palliative therapy, and supportive care; however, none of these treatment methods has provided satisfactory therapeutic effects when used alone. Case Report We report two cases of patients with EGJ carcinoma who were sequentially treated with immunotherapy plus induction chemotherapy, followed by immunotherapy plus concurrent chemoradiotherapy and maintenance immunotherapy. Both patients achieved extended overall survival times with good quality of life with this new therapeutic approach. Conclusion Immunotherapy plus chemoradiotherapy may therefore be a reasonable option for treatment of selected EGJ carcinoma patients. However, well-designed trials for the acquisition of additional evidence are required to validate the findings in this study.